Lithium lanthanum titanate perovskite as an anode for lithium ion batteries - Zhang, Lu; Zhang, Xiaohua; Tian, Guiying; Zhang, Qinghua; Knapp, Michael; Ehrenberg, Helmut; Chen, Gang; Shen, Zexiang; Yang, Guochun; Gu, Lin; Du, Fei (Nature communications, 2020)
Conventional lithium-ion batteries embrace graphite anodes which operate at potential as low as metallic lithium, subjected to poor rate capability and safety issues. Among possible alternatives, oxides based on titanium redox couple, such as spinel Li 4 Ti 5 O 12 , have received renewed attention. Here we further expand the horizon to include a perovskite structured titanate La 0.5 Li 0.5 TiO 3 into this promising family of anode materials. With average potential of around 1.0 V vs. Li + /Li, this anode exhibits high specific capacity of 225 mA h g −1 and sustains 3000 cycles involving a reversible phase transition. Without decrease the particle size from micro to nano scale, its rate performance has exceeded the nanostructured Li 4 Ti 5 O 12 . Further characterizations and calculations reveal that pseudocapacitance dictates the lithium storage process and the favorable ion and electronic transport is responsible for the rate enhancement. Our findings provide fresh impetus to the identification and development of titanium-based anode materials with desired electrochemical properties. Exploration of high performance materials for lithium storage presents as a critical challenge. Here authors report micron-sized La 0.5 Li 0.5 TiO 3 as a promising anode material, which demonstrates improved capacity, rate capability and suitable voltage as anode for lithium ion batteries.